2019
DOI: 10.25046/aj040445
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Bidding Strategy with Customized Pricing on the Individual Prosumer in a Local Energy Market

Abstract: Peer-to-peer (P2P) energy trading is a mechanism that allows people to share locally the energy they have generated from distributed renewable resources (DER), to generate profit form the unused resources and to reduce the cost for electricity for the household and in the community itself. This calls for the design of new energy markets, accompanied with the development of comprehensive exchange strategies, which reflect both the consumer?s preferences and the heterogeneity of the renewable sources. The paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…In the Quartierstrom trial in Switzerland, the self-sufficiency rate (SSR), or the proportion of energy demand met by the prosumers consuming their own energy, increased with P2P trading to 16.3%, compared to 15.5% in a scenario without trading [32]. Increased autarky was also achieved in a demonstration in Japan, a bidding strategy based on the current price of the electricity stored in the battery of each standalone system allowed those with medium or low consumption levels to be self-sufficient by making better use of their self-generated energy [33].…”
Section: Energy Independencementioning
confidence: 99%
See 1 more Smart Citation
“…In the Quartierstrom trial in Switzerland, the self-sufficiency rate (SSR), or the proportion of energy demand met by the prosumers consuming their own energy, increased with P2P trading to 16.3%, compared to 15.5% in a scenario without trading [32]. Increased autarky was also achieved in a demonstration in Japan, a bidding strategy based on the current price of the electricity stored in the battery of each standalone system allowed those with medium or low consumption levels to be self-sufficient by making better use of their self-generated energy [33].…”
Section: Energy Independencementioning
confidence: 99%
“…The trial in Japan demonstrated that, compared to a P2P bidding strategy with fixed prices, a bidding strategy based on the current price of the electricity stored in the battery of each standalone system resulted in 55% fewer deals due to fewer available matches in the preferred price range of participants and, in turn, a predictable pattern of stable peaks that indicate higher prices in comparison with the case of fixed pricing. However, the increased utilization of self-generated electricity achieved with the bidding strategy resulted in a 10% decrease in energy spending in households with high levels of consumption, and 7% decrease in medium and low consumption households of average daily consumption of more than 100 watts [33]. Other, less direct economic benefits can also follow, e.g., in India, local businesses benefit from being able to run larger loads [31].…”
Section: Economic Value Of P2p Csc and Te Modelsmentioning
confidence: 99%
“…End customer value − Autarky, self-sufficiency, or independence of energy supply [11][12][13][14][15][16][17] − Autonomy [11,15,[18][19][20][21][22][23] − Green energy [13,15,24] − Lower electricity costs [22][23][24][25][26] − Positive attitude to regionality [13,19,20,22,23] − Sense of community identity [27] − Intangible returns (built upon the notion of togetherness, friendship, love, solidarity, and different ways of bonding with others) [28,29] − Responsibility to future generation [15] − Sustainable lifestyle [21] − Desire for greater agency (active participation) in the energy transition [13,21,30,31] − Social comparison [13,15,30] − Perceived importance of shared generation and consumption and easy implementation [20] Business value − Make electricity less expensive, including making renewable energy more profitable and "supporting new and better mechanisms for return-on-investment beyond government subsidies" [13,[21]…”
Section: Levels Of Value Generation Type Of Value Referencesmentioning
confidence: 99%
“…Finally, there are the Energy Services Companies (ESCs) [75][76][77], an increasing category of companies offering their consultancy in electricity supply to the public [14].…”
mentioning
confidence: 99%
“…Optimization of electricity production and consumption schedule in a wholesale market where buyer and seller agents cooperate to determine the best energy contract, is one of such developmental research frameworks [42,43]. Current research also focuses on bilateral contract networks between suppliers and centralized producers [44]; computational properties of negotiation algorithms [45]; prosumers' behavioural pattern based on their bidding strategy [46]; optimized scheduling of energy storage for a P2P microgrid model using automated negotiations [47]; as well as enabling communication technologies [48]. Furthermore, agent-coordinated electricity trading between homes in a cooperative residential setting has been shown to lead to an overall battery capacity reduction and reduced energy losses [49,50].…”
Section: Introductionmentioning
confidence: 99%